Evaluation of the effects of amiodarone and amiodarone+dobutamine on survival in tilmicosin-induced toxicity by electrocardiography and biochemical parameters in goats: Survival rate in tilmicosin toxicity - Coskun, D; ider, M; naseri, A; Dik, B; Bahcivan, E; Tras, B; ER, ayse (Journal of the Hellenic Veterinary Medical Society, 2024)
Tilmicosin shows different degrees of cardiotoxic effect in various animal species depending on the route of administration and dose. We aimed to determine the effects of amiodarone and amiodarone+dobutamine treatments on tilmicosin cardiotoxicity and survival time. 18 healthy goats were divided into tilmicosin, tilmicosin+amiodarone and tilmicosin+amiodarone+dobutamine groups. After drug administrations, the survival times of the animals in all groups were recorded. In addition, blood was drawn from the animals just before they died. Haemogram, troponin I, CK-MB and other biochemical parameters were measured in all blood samples. Prolonged survival was observed in the treatment groups compared to the tilmicosin group. In the treatment groups, decreases in haemogram parameters, albumin, total protein and cholesterol levels caused by tilmicosin could not be prevented, while the increase in troponin I level was prevented. In conclusion, while cardiotoxicity due to high troponin from tilmicosin was prevented, the survival rate was not affected in both treatment groups, and the survival time was extended at differing rates. In case of accidental or deliberate overdose of tilmicosin in animals, in addition to the use of amiodarone+dobutamine, the survival time may be prolonged, and the success may increase if the necessary symptomatic treatments and equipment support are available.